(untitled) (Bangladesh Journal of Medical Science, 2016)
Background: Patient education is an important component of patient care. It includes all educational activities to help patients and their families in order to make informed decisions about the disease and learn self-care skills. This study was conducted to investigate nursing students perspectives regarding the challenges of patient education in clinical settings. Material and Methods: This descriptive cross-sectional study was conducted on 78 third and fourth year nursing students of Jahrom University of Medical Sciences who were selected by census method. Data were collected through a valid and reliable questionnaire consisted of four parts. The first part was about demographic data, the second included 16 questions about importance of patient education, the third and fourth part contained 20 questions about challenges of patient education, 10 questions assessed barriers and 10 questions were about facilitators of patient education in clinical settings. Results: From the nursing students perspective, the average importance of patient education was 4.36±0.05 out of 5. The most important challenges regarding barriers of patient education were; lack of resources and educational tools, lack of enough time, inadequate knowledge and skills of the nurse, and lack of patient readiness both physically and psychologically. Also, the most important facilitators were; high skill and knowledge, having interest to education and phased implementation of patients education with respect to the patients condition. There was no relationship between academic year, sex and average grade with importance of patient education total score (p=0>05). Conclusion: Nursing managers and educational supervisors of hospitals need to pursue patients education programs with rely on the standards developed at national and international accreditation programs as a major strategy and provide necessary resources and educational tools. Bangladesh Journal of Medical Science Vol.15(4) 2016 p.615-620